Economic Integration, Business Cycle, and Productivity in North America - Kose, Ayhan (IMF Working Papers; Working Paper ;, 2004)
This paper examines the effect of the major Canada-U.S. trade agreements on the dynamics of business cycles and productivity in Canada. The North American Free Trade Agreement (NAFTA) and its predecessor, the Canada-U.S. Free Trade Agreement (CUSFTA), have led to a substantial expansion of trade flows. Although common factors have played a larger role in explaining business cycles in Canada and the United States since the early 1980s, country-specific and idiosyncratic factors remain important for Canada. At the same time, while increased trade integration seems to have positively contributed to total factor productivity of Canadian industries, the persistence of structural differences between the two countries has prevented convergence of aggregate labor productivity. While these findings seem to weigh against moving toward a monetary union, they also suggest that substantial benefits could be reaped from further reducing remaining barriers to trade.